Implementing DDMRP in a Lebanese multiproduct industrial company - Joseph AL-AMMAR (Proche-Orient Études en management, 2019)
This article describes the implementation of DDMRP in a multiproduct industrial company. The term DDMRP, or Demand-driven MRP (Materials Requirements Planning) is a relatively new concept that is not well elaborated in the academic literature. The article reviews the academic literature, which, one has to note, is limited due to the young age of the concept. It will explore how the concept can be used as an inventory replenishment model by exploring its implementation at Liban Cables SAL – a Lebanese diversified multiproduct industrial company having to deal with different production cycles and processes.